Cardiac Autonomic Neuropathy Measured by Heart Rate Variability and Markers of Subclinical Atherosclerosis in Early Type 2 Diabetes. (4th December 2012) - Fakhrzadeh, Hossein; Yamini-Sharif, Ahmad; Sharifi, Farshad; Tajalizadekhoob, Yaser; Mirarefin, Mojde; Mohammadzadeh, Maryam; Sadeghian, Saeed; Badamchizadeh, Zohre; Larijani, Bagher
Abstract : Cardiac autonomic neuropathy (CAN) is a critical complication of type 2 diabetes mellitus (T2DM). Heart rate variability (HRV) is a noninvasive tool to assess cardiac autonomic function. We aimed to evaluate whether CAN is associated with increased risk of atherosclerosis in T2DM. A total of 57 diabetic and 54 nondiabetic subjects, free of coronary heart disease, were recruited. Carotid intima media thickness (CIMT), coronary calcium score (CAC), and brachial Flow Mediated Dilation (FMD) were measured. Heart rate variability and vagal components of autonomic function were determined. Significant reduction of normalized HF power ( P < 0.05 ) and total power ( P < 0.01 ) was observed in T2DM. CIMT and CAC scores were significantly higher while FMD was significantly lower in diabetics (P < 0.01 for all). Median HbA1c levels were significantly higher in diabetics. CIMT was inversely and independently associated with total power both in diabetics and controls (P < 0.01 for both groups). There was also an inverse association between total power and median HbA1c . Autonomic dysfunction, especially parasympathetic neuropathy, was present since early-stage T2DM. This was related to subclinical atherosclerosis. Early detection of cardiac autonomic neuropathy can help us detect the development of atherosclerosis earlier in T2DM to prevent unfavorable outcomes.